MSoDIM: Multiple Sources of Data Integration Model for Mud Crabs in SetiuWetland - Wan Aezwani, Wan Abu Bakar; Mustafa, Man (2019)
Data integration is the process of combining data from different sources into a single, unified view. Integration begins with the ingestion process, and includes cleansing, Extract-Transform-Load (ETL) mapping, and transformation. Data integration is one of the most prominent issues to be solved especially in integrating unstructured or structured data with multiple types and formats. This paper introduces a new model for integrating multiple types of heterogeneous data applying to mud crabs case study in Setiu Wetland (SW). MSoDIM model is a three-tier architecture of mud crabs data warehouse. Simulation result shows that the processing time for integration of unstructured biodiversity data of mud crabs in MySQL and MSSQL servers are lesser than 1.5 seconds for 12 rows of 7 MB data.